Ocular Complications of Myopia: Bibliometric Analysis and Citation Networks - Miguel Ángel Sánchez-Tena; Clara Martinez-Perez; Cesar Villa-Collar; Cristina Alvarez-Peregrina (Reports, 2023)
Background: The objective of this study is to determine the relationship between publications and authors. In turn, the different areas of research on the ocular complications of myopia are also identified, and the most cited publication by citation networks is determined. Methods: The search for publications is carried out in the Web of Science database using the term “myopia OR nearsightedness AND retin* OR degenerat* OR detachment OR patholog* OR glaucoma OR cataract OR machulopathy OR “choroidal neovascularization” for the period between 1978 and December 2022. Publication analysis was performed using the Citation Network Explorer, VOSviewer and CiteSpace software. Results: A total of 9357 publications and 78,400 citation networks were found across the network, with 2021 being the year with the highest number of publications, 712. The most cited publication was “Myopia”, published in The Lancet journal in 2012 by Morgan et al. with a citation index of 1006. By using the clustering function, seven groups covering the different research areas in this field were found: axial growth of the eye; myopic maculopathy; ocular complications in patients with myopia after a surgery; glaucoma; retinal detachment; cataracts and retinopathy of prematurity. Conclusions: The citation network offers a quantitative and qualitative analysis of the main papers on ocular complications of myopia. The research on this field is multidisciplinary; however, the main topic studied is the axial growth of the eye.